2015
DOI: 10.4236/aim.2015.53015
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Campylobacteriosis in the Northern Region of India

Abstract: Campylobacter is one of the most common bacterial enteropathogens of food borne origin in industrialized countries with C. jejuni being the most common species followed by C. coli. The prevalence of Campylobacters in and around Chandigarh, India was studied by phenotypic and genotypic methods. Fecal samples from 1145 diarrheal patients and 102 healthy subjects from hospital and community were cultured on Campylobacter media and identified by Gram stain, biochemical investigations and serotyping. Molecular iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In this study, the prevalence of campylobacter in chicken meat samples was 32% which is similar to that found in Gauteng, South Africa, 32.3% (Van Nierop et al, 2005) and lower than rates in Spain in which campylobacter isolated with percentage of 49.5% from chicken meat samples (Dominguez et al, 2002). Poultry can be contaminated from a variety of sources on farms and the contaminants are spread during processing, scalding, defeathering, evisceration and giblet operations are major points of spread, further spread can occur during handling in markets and kitchens.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, the prevalence of campylobacter in chicken meat samples was 32% which is similar to that found in Gauteng, South Africa, 32.3% (Van Nierop et al, 2005) and lower than rates in Spain in which campylobacter isolated with percentage of 49.5% from chicken meat samples (Dominguez et al, 2002). Poultry can be contaminated from a variety of sources on farms and the contaminants are spread during processing, scalding, defeathering, evisceration and giblet operations are major points of spread, further spread can occur during handling in markets and kitchens.…”
Section: Discussionsupporting
confidence: 85%
“…or sub-lethal injury with or without reduction in viable counts under investigated storage temperatures which may indicates the ability of campylobacter to survive in chicken meat stored under refrigerated and frozen conditions (Eideh and Al-Qadiri, 2011), also, may be due to oxidative stress contribute to the freeze-thaw induced killing of campylobacter (Stead and Park, 2000). Prevalence of campylobacter in human diarrheal samples was 14.7% which are higher than results of Bangkok and its suburb in Thailand, 3% (Samosornsuk et al, 2015), and results of northern region of India, 2.6% (Vaishnavi et al, 2015) and lower than results obtained in Indonesia which was 79.5% (Pagaya et al, 2015) and that obtained in Pakistan which was 30% (Guhar et al, 2015), variations of rates in various parts of the world may be due to the varying standards and styles of living conditions, water supply and feeding habits. Rate of campylobacter in children was 17.5% which was lower than results in Egypt which was 35% (Barakat et al, 2015), higher than results of India which was 10% (Salim et al, 2014) and similar to results of northern Thailand which was 18% (Padungtod and Kaneene, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Global Enteric Multicenter Study (GEMS) conducted in Asia and Africa revealed that C. jejuni was the fourth, fifth and third highest cause of diarrhoea in the first year of life among children from Bangladesh, Pakistan, and India respectively [15]. Other studies from India have reported Campylobacter infections in 1.5-17 % of the diarrhoeal cases in humans with C. jejuni and C. coli being the predominant species [6,[16][17][18][19][20]. Campylobacter is also the leading cause of travellers' diarrhoea, and often shows seasonal variation [21].…”
Section: Introductionmentioning
confidence: 99%
“…jejuni and C. coli being the predominant species [6, 16–20]. Campylobacter is also the leading cause of travellers' diarrhoea, and often shows seasonal variation [21].…”
Section: Introductionmentioning
confidence: 99%
“…in the poultry reservoir is a crucial step in prevention and control of food-borne campylobacteriosis in humans. Other possible sources like contaminated drinking water, consumption of unpasteurized milk and ready to eat food products, faecal run-off of birds and domestic animals contaminating surface water and direct contact with animals are signi cant in transmitting illness to humans (9).…”
Section: Introductionmentioning
confidence: 99%